Partial replacement of Chemical Fertilizers with Organic and Biofertilizers of Anabaena circcinalis and Oscillatoria lymentica in rice Fields. - Burjus , Sanaa j.; Rasheed, Firas T.; Mahdy, Mohammad S. (Iraqi Journal of Science, 2022)
A field experiment was carried out in the province of Najaf - al ashraf using two types of blue-green algae( Anabaena circinalis and Oscillaoria lymentica) which have been isolated and diagnosed in the laboratories of the department of plant protection / ministry of agriculture in Iraq with the compost( palm fronds ) manufacturer locally and by 1 ml : 10 g of organic matter within one month of cuddling and using a single level of humidity is 1 : 2 (water : organic matter). Randomized complete block design RCBD to see the effect of use it as a single or mix in the productivity of rice crop Yasamin cultivar where it was noted that it is equipped with a dynamic composting of organic matter leads to the analysis of organic material and increasing the nitrogen content to moss 32.76 % with Anabaena and 19.72 % with mixture of algae. It was also observed superiority of the treatment (5) Anabaena with 25% of the chemical fertilizer, treatment (4) Anabaena with 50% of the chemical fertilizer which is not differ with the treatment (2) full recommending fertilizer and treatment (9) compost with 50% of the recommendation fertilizer, which gave seed weight 695 g / m2 and 694 g / m2 , respectively, compared with 754.7 g/m2 and 730 g/m2 respectively, Weight of 1000 also gave the seed of 27.64 g and 27.58 g, respectively, compared with 754.7 g and 730 g, respectively the length of the deltoid was 25.23 cm and 24.70 cm, respectively, compared with 25.37 cm and 25.30 cm respectively and it was noted an increase in the biological yield gave 15.88 tons / h and 15.84 tons /h, respectively, compared to 16.50 tons/h and 16.13 tons /h. Also it was noted an increase in the length of plant in treatment (4) Anabaena with 50% of the fertilizer recommendation which is not differ with the full treatment of recommendation fertilizer and the treatment 9 of compost with 50% of the recommendation as fertilizer gave 110.6 cm compared to 110.9 cm and 110.1cmrespectively, as for the dry weight observed increasing of algae treatments (4) treatment Anabaena with 50% of the recommendation fertilizer ,(5) treatment Anabaena with 25% of the recommendation fertilizer and (7) treatments (algae mixture with 50% of the fertilizer recommendation) which is not differ from full recommending fertilizer (2) treatment and (9) treatment compost with 50% of the recommendation fertilizer, was given 890 g 893 g, 890 g, respectively, compared to 896 g and 883 g, respectively.We conclude that the use of the way with bio- organic and algal fertilizer in alone or mixture increase in productivity of growth ,biological yield and reduces the use of chemical fertilizer for a healthy quotient of consumers in food consumption.